Health vigilance concerning female urinary tract infections: Epidemiological profile and antibiotic resistance - Farih Soumaia (EDP Sciences, 2021)
The objectives of our work were to establish the epidemiological and bacteriological profile of female urinary tract infection at the Mohammed VI University Hospital of Oujda (Morocco), and then to study the drug resistance of the bacterial strains isolated. This is a retrospective study over 36 months including urine samples from patients hospitalized or consulting at the CHU Mohamed VI of Oujda (Morocco). Urines were processed according to the recommendations of the Medical Microbiology Reference (REMIC) and the EUCAST (European Committee on Antimicrobial Susceptibility Testing). We collected 12556 requests for CBEU from different departments. At the top of the list was the emergency department with a rate of 37% (n= 4666) followed by outpatient clinics (33.1%; n=4226). 5% (n=630) of the CBEU were positive. Escherichia coli (E. coli ) dominated the epidemiological profile with a rate of 72.50% (n=482). E. coli was resistant to penicillins in 69.50% (n=299) of cases, protected penicillins in 34.80% (n=149), third generation cephalosporins (C3G) in 9% (n=38), fluoroquinolones in 17.5% (n=73), Trimethoprim-Sulfamethoxazole in 46% (n=196) of cases and gentamicin in 12% (n=51) of cases. None of the strains were resistant to carbapenems. Awareness-raising on the proper use of antibiotics, issuing national recommendations for the treatment of urinary tract infections in order to standardize therapeutic regimens. Effective control of these infections requires a global prevention strategy that implies close collaboration between epidemiologists, clinicians, bacteriologists, hygienists and the health care team.